Modification of Composition and Properties of Blend of Soyphospholipid and Coconut oil by Enzymatic Interesterification for Better Food Use - G. Saha; D. K. Bhattacharyya; M. Ghosh (Current Perspectives on Chemical Sciences Vol. 8, 2021)
The fatty acid composition (FAC) of both soyphospholipid (SPL) and coconut oil (CO) was modified by enzymatic interesterification simultaneously. Significant modifications were observed in FAC where in modified soyphospholipid (MSPL), the extent of incorporation of caprylic, capric and lauric acids were 5.735 ± 0.31%, 14.39 ± 0.15% and 7.945 ± 0.13% respectively and in modified coconut oil (MCO) the extent of incorporation of linoleic and linolenic acids were 6.625 ± 0.3% and 1.58 ± 0.35%. Other properties in terms of antioxidant activity of the modified products were determined and significant changes were detected compared to the original SPL and CO. The surface active property such as surface tension was measured in case of modified soyphospholipid (MSPL) product that got reduced by about 4 units. This lowering of surface tension for MSPL can be useful as an emulsifier effective for food use.